The Influence of Innovative Behavior, Employee Engagement, Entrepreneur Self-Efficacy on the Performance of UMKM UD Sumber Rejeki - Diansyah, Reni Nur; Abadiyah, Rifdah; Andriani, Dewi (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This research analyzes the influence of innovative behavior, Employe engagement, Entrepreneur self efficacy on the performance of UMKM UD Sumber Rejeki. Business growth in the small industrial sector requires companies to innovate and adapt. Excellent human potential is an important factor in achieving this development. This research used a quantitative method with a saturated sampling approach involving 90 UD Sumber Rejeki employee respondents. Data collection was carried out using a questionnaire that calculated respondents' attitudes and views using a Likert scale. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3.2.8 software to test the hypothesis. The research results show that innovative behavior, employee engagement, entrepreneurial self-efficacy have a positive and significant effect on employee performance.